The Effect of Financial Literacy, Self-Control, and Parental Income on Financial Behavior - Aprillia Fananditya; Dwi Eko Waluyo (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study analyzes the influence of financial knowledge, self-control, and parental income on the financial behavior of students in Semarang, Central Java, with a population consisting of active students and a sample of 305 respondents. This quantitative study utilizes data obtained through Google Forms and analyzed using the Smart PLS 4 method. Measurements were made using a Likert scale from 1 to 5 for each indicator. The findings of this study indicate that financial knowledge and self-control have a significant and positive influence on financial behavior, with path coefficients of 0.417 and 0.303, respectively, and a p-value of 0.000. Parental income also has a significant impact on financial behavior with 90% confidence, although the path coefficient is lower at 0.078 and the p-value is 0.099. Overall, the three independent variables (financial competence, self-control, and parental income) together contribute 60% in explaining the variation in financial behavior. The remaining 40% is influenced by other factors outside the research model. This conclusion emphasizes that internal factors such as knowledge and self-control are very important, but family economic background also plays a role in shaping individual financial habits and decisions.